2019
DOI: 10.1016/j.neuroimage.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynamics and temporal trajectories during task and naturalistic processing

Abstract: Human functional Magnetic Resonance Imaging (fMRI) data are acquired while participants engage in diverse perceptual, motor, cognitive, and emotional tasks. Although data are acquired temporally, they are most often treated in a quasi-static manner. Yet, a fuller understanding of the mechanisms that support mental functions necessitates the characterization of dynamic properties. Here, we describe an approach employing a class of recurrent neural networks called reservoir computing, and show the feasibility an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Another weakness of this study is that we did not directly compare our approach to other representations created from fMRI time series. For example, representations generated from the fMRI time series using reservoir computing have been shown to discriminate between 2-back and 0-back task conditions with 77-81% accuracy (Venkatesh et al, 2019). Nevertheless, we feel that the brain networks reveal important neural processes that are captured only by examining the relationships between brain regions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another weakness of this study is that we did not directly compare our approach to other representations created from fMRI time series. For example, representations generated from the fMRI time series using reservoir computing have been shown to discriminate between 2-back and 0-back task conditions with 77-81% accuracy (Venkatesh et al, 2019). Nevertheless, we feel that the brain networks reveal important neural processes that are captured only by examining the relationships between brain regions.…”
Section: Discussionmentioning
confidence: 97%
“…There is a growing interest in studying and visualizing brain dynamics in low-dimensional space, but most studies have directly examined the fMRI time series, rather than dynamic networks. Principal components analysis (PCA) has been used to reduce the dimensionality of the raw fMRI data (Shine et al, 2019), and reservoir computing (Venkatesh et al, 2019) has been used to examine temporal state transitions in the raw fMRI data. Both of these studies demonstrated that the patterns of dynamic transitions were unique for distinct task conditions.…”
Section: Introductionmentioning
confidence: 99%
“…If the top three dimensions are selected, the evolution of the reservoir can be plotted in this lower-dimensional space. In the present case, the trajectories originated from functional MRI data during the viewing of short movie clips, which were either "scary" or "funny" (Venkatesh et al, 2019). In the example, the trajectories separated quite well.…”
Section: Learning Dynamics With Reservoir Computingmentioning
confidence: 70%
“…But can trajectories be learned from neural data? In this section, we describe an approach to learning temporal information that we recently developed in the context of functional MRI data (Venkatesh et al, 2019).…”
Section: Learning Dynamics With Reservoir Computingmentioning
confidence: 99%
See 1 more Smart Citation